Special large-size graphite electrode for metal silicon smelting and preparation method of special large-size graphite electrode

By using high-temperature modified asphalt and aldehyde-based nanomaterials as binders, combined with optimized calcination and graphitization processes, the problem of poor performance of large-scale graphite electrodes is solved, and the effects of low resistivity, high strength and high thermal performance are achieved.

CN119462154APending Publication Date: 2025-02-18HEBEI LIANJING CARBON NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411616112.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing large-size graphite electrodes have problems such as high air permeability, high resistivity, poor mechanical and thermal properties in metal silicon smelting, mainly due to poor adhesive properties and high volatility of high temperature asphalt.

Method used

Using high-temperature modified asphalt as a binder, the nanomaterials such as graphene, carbon nanotubes and molybdenum disilide are combined with epoxy macromolecular silane coupling agent to form aldehyde-based nanomaterials, and high-temperature asphalt is modified to improve its Kneading properties and residual carbon ratio, and the performance of the electrode is improved by optimizing the calcination and graphitization processes.

Benefits of technology

The air permeability and resistivity of large-size graphite electrodes are significantly reduced, and their mechanical and thermal properties are improved, making the electrodes safer and more reliable in industrial silicon furnaces.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a large-size graphite electrode special for metal silicon smelting and a preparation method of the large-size graphite electrode, and relates to the technical field of graphite electrodes. The preparation method comprises the following steps: 1, uniformly dry-mixing calcined petroleum coke and broken electrode graphite, adding high-temperature modified asphalt, heating and kneading to obtain a paste material; step 2, cooling the paste to 130-140 DEG C, adopting a vertical vibration and horizontal extrusion molding process, firstly pressing and then vibrating under the vertical pressure of 17-22 kg / cm < 2 >, cooling in a cold water pool for 6-8 hours, discharging water and standing for 48 hours to obtain an electrode premise; and 3, carrying out roasting treatment and graphitization treatment on the electrode to obtain the large-size graphite electrode. In the application, the nano material with a specific proportion is introduced into the high-temperature modified asphalt, and the subsequent roasting and graphitization optimization process is cooperated, so that the orientation and carbonization of the asphalt adhesive are effectively promoted, the density is improved, the resistivity is reduced, and the performance of the large-size graphite electrode is comprehensively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of graphite electrodes, in particular to a large-scale graphite electrode specially used for metal silicon smelting and a preparation method thereof. Background Art

[0002] In recent years, with the development of solar energy and photovoltaic industries, the demand and application of silicon raw materials such as monocrystalline silicon and polycrystalline silicon have increased day by day, which has greatly promoted the development of silicon raw materials in production and other aspects. At present, in the smelting of metallic silicon, the restriction of electrode specifications on the capacity of electric furnaces has constrained its rapid development; therefore, based on meeting the diameter requirements and application performance of graphite electrodes used in large industrial silicon smelting furnaces, it is urgent to increase the capacity of industrial silicon furnaces, increase the radius of silicon furnace electrode crucibles, and manufacture large-size electrodes for large industrial silicon furnaces.

[0003] In the prior art, graphite electrodes are usually kneaded by mixing graphite crumbs, tar, and binders, and then calcined and graphitized. Since large-scale graphite electrodes are large in size and require more raw materials, there are problems such as poor kneading dispersion and low interfacial effect, which results in poor performance of the electrodes after graphitization. Among them, the binder is one of the keys to this problem; generally, the binder is required to have good kneading fluidity, high interfacial effect, and high residual carbon. A common binder is asphalt; however, the current high-temperature asphalt has the defects of poor binder properties and high volatile matter; this will cause the large-scale graphite electrodes prepared to have a high air permeability, resulting in a high resistivity, poor mechanical properties, and poor thermal properties.

[0004] In summary, it is of great significance to solve the above problems and prepare a large-scale graphite electrode specially used for metallic silicon smelting. Summary of the invention

[0005] The purpose of the present invention is to provide a large-scale graphite electrode specially used for metal silicon smelting and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A method for preparing a large-scale graphite electrode specially used for metal silicon smelting comprises the following steps:

[0008] Step 1: Evenly dry-mix calcined petroleum coke and electrode graphite, add high-temperature modified asphalt, heat to 140-150° C. and knead for 15-30 minutes, heat to 160-170° C. and knead for 10-20 minutes to obtain a paste;

[0009] Step 2: Cool the paste to 130-140℃, and use vertical vibration horizontal extrusion molding process with vertical pressure of 17-22 kg / cm 2Press first and then vibrate, cool in cold water pool for 6-8 hours, let stand for 48 hours to obtain electrode prerequisites;

[0010] Step 3: calcining and graphitizing the electrode to obtain a large-sized graphite electrode.

[0011] More optimally, during the calcination process, a heating curve of 1100 to 1250 hours is set to heat to 880 to 900°C, calcined for 200 to 300 hours, and naturally cooled out of the furnace to obtain a calcined product; during the graphitization process, a heating rate of 10 to 15°C / min is set to heat to 2400 to 2800°C, power is supplied for 50 to 80 hours, power is cut off, and cooled to obtain a large-sized graphite electrode.

[0012] More optimally, the raw materials of the paste include the following components: by weight, 75-80 parts of calcined petroleum coke, 20-25 parts of electrode graphite chips, and 20-30 parts of high-temperature modified asphalt;

[0013] The calcined petroleum coke includes materials of the following particle sizes: 40 to 50 parts of calcined petroleum coke A with a size of 1 to 10 mm, and 30 to 35 parts of calcined petroleum coke B with a size of 0.1 to 0.15 mm; the electrode graphite fragments include materials of the following particle sizes: 9 to 12 parts of electrode graphite fragments A with a size of 0.1 to 4 mm, 5 to 7 parts of electrode graphite fragments B with a size of 4 to 8 mm, and 4 to 6 parts of electrode graphite fragments C with a size of 8 to 15 mm.

[0014] More optimally, the preparation method of the high temperature modified asphalt is:

[0015] Step 1: (1) Add nanomaterials and epoxy macromolecular silane coupling agent to anhydrous toluene, and drop triethylamine; reflux at 110-115° C. for 2-3 hours under nitrogen atmosphere; wash and dry to obtain modified nanomaterials; (2) Add the modified nanomaterials to 0.1-0.12 mol / L sulfuric acid solution, heat to 50-55° C., stir for 6-8 hours, filter and wash to obtain preactivated nanomaterials; (3) Disperse the preactivated nanomaterials in deionized water, add 0.1-0.12 mol / L sodium periodate solution, stir at room temperature for 4-6 hours; wash and dry to obtain aldehyde-modified nanomaterials;

[0016] Step 2: Evenly mix the high-temperature asphalt, anthracene oil, trioxymethylene, aldehyde-modified nanomaterials, and p-toluenesulfonic acid; in a nitrogen atmosphere, heat to 140-160° C. and stir for 18-24 hours, then stop heating to obtain high-temperature modified asphalt.

[0017] More optimally, the nanomaterial includes graphene, carbon nanotubes, and molybdenum disilicide in a mass ratio of 0.5-0.6:0.2-0.3:0.1.

[0018] More optimally, the raw materials of the high-temperature modified asphalt include the following components: by mass, 55 parts of high-temperature asphalt, 15-20 parts of anthracene oil, 5-8 parts of trioxymethylene, 12-15 parts of formaldehyde-modified nanomaterials, and 10-12 parts of p-toluenesulfonic acid.

[0019] More optimally, in the raw materials of the modified nanomaterial, the ratio of nanomaterial, epoxy macromolecular silane coupling agent, and triethylamine is 1g:6-8mL:0.15-0.18mL; in the raw materials of the preactivated nanomaterial, the ratio of modified nanomaterial and sulfuric acid solution is 1g:18-20mL; in the raw materials of the formaldehyde-treated nanomaterial, the ratio of preactivated nanomaterial, deionized water, and sodium periodate solution is 1g:18-20mL:4-4.5mL.

[0020] More optimally, the preparation method of the epoxy macromolecular silane coupling agent is:

[0021] S1-1: Sodium sand, 1,2-dimethyl-1,1,2,2-tetrachlorodisilane, and diethylene glycol dimethyl ether are sequentially added to tetrahydrofuran, and stirred at room temperature for 5 to 8 minutes under a nitrogen atmosphere; the temperature is raised to 40 to 50°C; methylvinyldichlorosilane, methylphenyldichlorosilane, and dibromomethane are added dropwise; after the addition is completed, the reaction is continued for 3 to 4 hours; chlorodimethylsilane borate and trimethylchlorosilane are added sequentially, and stirring is continued for 0.5 to 1 hour; suction filtration, washing, and reduced pressure distillation are performed to obtain liquid vinyl polycarbosilane;

[0022] S1-2: Add liquid vinyl polycarbosilane and formic acid to toluene, add concentrated sulfuric acid dropwise; raise the temperature to 30-35°C, add hydrogen peroxide dropwise; raise the temperature to 60-70°C to react for 4-6 hours; wash to neutrality, evaporate the solvent, and obtain epoxy polycarbosilane;

[0023] S1-3: Add epoxy polycarbosilane, amino silane coupling agent and ferrocenylamine to toluene in sequence, raise the temperature to 60-65° C. and react for 6-8 hours, evaporate the solvent to obtain an epoxy macromolecular silane coupling agent.

[0024] More optimally, the raw materials of the liquid vinyl polycarbosilane include the following components: by mass fraction, 3 to 4 parts of sodium sand, 3 to 5 parts of 1,2-dimethyl-1,1,2,2-tetrachlorodisilane, 14 to 17 parts of methylvinyldichlorosilane, 12 to 15 parts of methylphenyldichlorosilane, 34 to 38 parts of dibromomethane, 6 to 8 parts of chlorodimethylsilane borate, 4 to 6 parts of trimethylchlorosilane, 5 to 10 parts of diethylene glycol dimethyl ether, and 125 to 130 parts of tetrahydrofuran;

[0025] The raw materials of the epoxy polycarbosilane include the following components: by mass fraction, 10 parts of liquid vinyl polycarbosilane, 1.5-1.8 parts of formic acid, 0.2-0.5 parts of concentrated sulfuric acid, and 6-7 parts of hydrogen peroxide; the raw materials of the epoxy macromolecular silane coupling agent include 10 parts of epoxy polycarbosilane, 0.3-0.5 parts of aminosilane coupling agent, and 0.05-0.08 parts of ferroceneamine.

[0026] Compared with the prior art, the beneficial effects achieved by the present invention are as follows:

[0027] (1) The scheme uses high-quality calcined petroleum coke, adds a certain proportion of electrode graphite, and uses high-temperature modified asphalt as a binder; optimizes the ratio and performs two-stage kneading to ensure the homogeneity and good plasticity of the kneaded paste; adopts a vertical vibration horizontal extrusion molding process to ensure the density and homogeneity of the electrode; and uses a cold water pool for cooling after molding, and allows the electrode precursor to stand still after being discharged from the water, so as to effectively release the pressure component of the electrode precursor; by controlling the heating curve or rate of the roasting and graphitization process, and controlling the temperature and time, the performance of the graphite electrode product during the processing is kept uniform; so that the resistivity of the prepared large-scale electrode is less than 12μΩ . m, thermal expansion coefficient is 2.6~2.9×10 -6 The thermal expansion gap between the male and female buckles and the cross-sectional gap of the electrodes is 0.1 to 0.4 mm, ensuring that the two electrodes are tightly butted and evenly connected, so that the electrodes can be used safely on industrial silicon furnaces without breaking.

[0028] (2) In the present application, nanomaterials are used to modify high-temperature asphalt to obtain high-temperature modified asphalt; it is used as a binder to effectively improve the kneading properties of the electrode precursor and increase the residual carbon of the binder; it is effectively reduced The air permeability after graphitization; the resistivity of large-scale graphite electrodes is reduced, and their mechanical properties or thermal properties are improved.

[0029] Among them, due to the dispersion and agglomeration problems of nanomaterials, the nanomaterials are surface-modified with epoxy macromolecular silane coupling agents, and then the epoxy groups are reacted to form aldehyde groups, thereby obtaining aldehyde-modified nanomaterials and introducing them into high-temperature asphalt. By utilizing the dispersion of high-temperature modified asphalt in the electrode premise, the nanomaterials are effectively dispersed evenly in the premise, thereby improving the performance of the graphite electrode.

[0030] Among them, aldehyde-based nanomaterials are used to cross-link and polymerize high-temperature asphalt; anthracene oil modification can increase the fluidity of the modified asphalt, facilitate kneading, and improve the interfacial adhesion of the asphalt. The introduced aldehyde-based nanomaterials can improve the bonding cohesive strength, inhibit the volatilization of the high-temperature phase, maximize the retention of residual carbon, reduce the air reaction yield, and reduce the electrode resistivity.

[0031] First, the nanomaterial is composed of graphene, carbon nanotubes, and molybdenum disilicide; the three can act as structure-directing agents to effectively catalyze the carbonization of high-temperature modified asphalt, thereby forming a highly conductive and carbon-based electric heating material. The addition of graphene can effectively promote graphitization, effectively increase the sp2 carbon content, and reduce defects. The morphology of carbon nanotubes is different from that of graphene. Its introduction can increase the carrier concentration after carbonization and improve the conductivity; at the same time, it is embedded in the graphite electrode, which can promote the subsequent release of external forces and improve the mechanical strength. The introduction of molybdenum disilicide, due to the introduction of epoxy macromolecular silane coupling agents containing polycarbosilane segments during the modification process, can promote the formation of nano-sized SiC grains, improve density, relieve the pressure of tiny pores, and improve mechanical properties; and it has molybdenum ions that can improve the thermal conductivity and electrical conductivity of graphite electrodes.

[0032] Secondly, the epoxy macromolecular silane coupling agent is based on esterified liquid vinyl polycarbosilane, which is obtained by epoxidation and then grafting aminosilane coupling agent and ferrocenylamine to some epoxy groups. It contains the main chain of liquid vinyl polycarbosilane, which can improve the bonding performance of asphalt and reduce the volatility of asphalt after being introduced into high-temperature asphalt; and the main chain is C-Si-C main chain with low oxygen content, which can subsequently produce silicon carbide to improve mechanical properties, reduce the thermal expansion coefficient of graphite electrodes, and improve its stability under temperature changes. In addition, liquid vinyl polycarbosilane contains boron groups and is grafted with iron-containing segments; low boron content can increase the number of p-type carriers in graphite carbon and improve conductivity; and iron-containing synergistic molybdenum disilicide effectively catalyzes and promotes the growth of graphite crystallites, improves the degree of graphitization and order, and increases conductivity and thermal stability. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] It should be noted that the following parts are calculated by weight, and the purchase manufacturers of all raw materials involved in the present invention are exemplary included without any special restrictions: In the following embodiments, the CAS number of ferrocenylamine is 1273-82-1; the original specification of high-temperature asphalt is 0-3mm, purchased from Hebei Xiangbei New Material Technology Co., Ltd.; it is crushed and ground before use, and used after passing through a sieve with a pore size of 0.2mm. The specification of calcined petroleum coke A is 1-10mm; the specification of calcined petroleum coke B is 0.1-0.15mm; the specification of electrode graphite A is 0.1-4mm; the specification of electrode graphite B is 4-8mm; the specification of electrode graphite C is 8-15mm. The mass fraction of hydrogen peroxide is 30%. In addition, the remaining raw materials are commercially purchased.

[0035] Unless otherwise specified, in the following embodiments, the preparation process of the aldehyde-modified nanomaterial is as follows:

[0036] Step 1: (1) 3.5 g of sodium sand, 3.2 g of 1,2-dimethyl-1,1,2,2-tetrachlorodisilane, and 10 g of diethylene glycol dimethyl ether were sequentially added to 130 g of tetrahydrofuran, and stirred at room temperature for 5 minutes under a nitrogen atmosphere; the temperature was raised to 50° C.; 16 g of methylvinyldichlorosilane, 13 g of methylphenyldichlorosilane, and 36 g of dibromomethane were added dropwise; after the addition was completed, the reaction was continued for 4 hours; 6 g of chlorodimethylsilane borate and 5 g of trimethylchlorosilane were added sequentially, and stirring was continued for 1 hour; suction filtration, washing, and reduced pressure distillation were performed to obtain to liquid vinyl polycarbosilane; (2) adding 10g of liquid vinyl polycarbosilane and 1.6g of formic acid to toluene, and dropping 0.32g of concentrated sulfuric acid; heating to 35°C, dropping 6.9g of hydrogen peroxide; heating to 65°C for reaction for 6 hours; washing to neutrality, evaporating the solvent to obtain epoxy polycarbosilane; (3) adding 10g of epoxy polycarbosilane, 0.5g of γ-aminopropyl triethoxysilane, and 20.05g of ferrocenylamine to toluene in sequence, heating to 60°C for reaction for 6 hours, evaporating the solvent to obtain an epoxy macromolecular silane coupling agent;

[0037] Step 2: (1) Graphene, carbon nanotubes and molybdenum disilicide are mixed uniformly in a mass ratio of 0.6:0.3:0.1 to obtain a nanomaterial; (2) 1 g of the nanomaterial and 8 mL of an epoxy macromolecular silane coupling agent are added to 10 mL of anhydrous toluene, and 0.16 mL of triethylamine is added dropwise; under a nitrogen atmosphere, refluxed at 110° C. for 3 hours; washed and dried to obtain a modified nanomaterial; (3) 1 g of the modified nanomaterial is added to 20 mL of a 0.1 mol / L sulfuric acid solution, heated to 50° C. and stirred for 8 hours, filtered and washed to obtain a preactivated nanomaterial; (4) 1 g of the preactivated nanomaterial is dispersed in 20 mL of deionized water, 4.5 mL of a 0.1 mol / L sodium periodate solution is added, and stirred at room temperature for 5 hours; washed and dried to obtain an aldehyde-modified nanomaterial;

[0038] The process can be scaled up.

[0039] Embodiment 1: A method for preparing a large-scale graphite electrode for metal silicon smelting, comprising the following steps:

[0040] Pre-preparation: 55 parts of high-temperature asphalt, 16 parts of anthracene oil, 5 parts of trioxymethylene, 14 parts of formaldehyde-modified nanomaterials, and 10 parts of p-toluenesulfonic acid were mixed evenly; heated to 150°C and stirred for 20 hours under a nitrogen atmosphere, and then the heating was stopped to obtain high-temperature modified asphalt;

[0041] Step 1: dry-mix 78 parts of calcined petroleum coke (45 parts of calcined petroleum coke A and 33 parts of calcined petroleum coke B) and 22 parts of electrode graphite crumbs (10 parts of electrode graphite crumbs A, 7 parts of electrode graphite crumbs B, and 5 parts of electrode graphite crumbs C), add 26 parts of high-temperature modified asphalt, heat to 150° C. and knead for 30 minutes, heat to 170° C. and knead for 15 minutes to obtain a paste;

[0042] Step 2: Cool the paste to 140°C and use vertical vibration horizontal extrusion molding process with a vertical pressure of 20 kg / cm 2 Press first and then vibrate, cool in cold water pool for 6 hours, let stand for 48 hours to obtain electrode premise;

[0043] Step 3: The electrode is calcined, during which: a 1250-hour heating curve is set to heat to 900°C, calcined for 250 hours, naturally cooled and taken out of the furnace to obtain a calcined product; then it is graphitized, during which: a heating rate is set to 10°C / min to heat to 2600°C, power is supplied for 60 hours, power is cut off, cooled, and a large-sized graphite electrode is obtained.

[0044] Embodiment 2: A method for preparing a large-scale graphite electrode for metal silicon smelting, comprising the following steps:

[0045] Pre-preparation: 55 parts of high-temperature asphalt, 20 parts of anthracene oil, 8 parts of trioxymethylene, 15 parts of formaldehyde-modified nanomaterials, and 12 parts of p-toluenesulfonic acid were mixed evenly; heated to 150°C and stirred for 20 hours under a nitrogen atmosphere, and then the heating was stopped to obtain high-temperature modified asphalt;

[0046] Step 1: dry-mix 80 parts of calcined petroleum coke (50 parts of calcined petroleum coke A and 30 parts of calcined petroleum coke B) and 20 parts of electrode graphite crumbs (9 parts of electrode graphite crumbs A, 7 parts of electrode graphite crumbs B, and 4 parts of electrode graphite crumbs C), add 30 parts of high-temperature modified asphalt, heat to 150° C. and knead for 30 minutes, heat to 170° C. and knead for 15 minutes to obtain a paste;

[0047] Step 2: Cool the paste to 140°C and use vertical vibration horizontal extrusion molding process with a vertical pressure of 20 kg / cm 2Press first and then vibrate, cool in cold water pool for 6 hours, let stand for 48 hours to obtain electrode premise;

[0048] Step 3: The electrode is calcined, during which: a 1200-hour heating curve is set to heat to 880°C, calcined for 250 hours, naturally cooled and taken out of the furnace to obtain a calcined product; then it is graphitized, during which: a heating rate is set to 10°C / min to heat to 2600°C, power is supplied for 60 hours, power is cut off, cooled, and a large-sized graphite electrode is obtained.

[0049] Embodiment 3: A method for preparing a large-scale graphite electrode for metal silicon smelting, comprising the following steps:

[0050] Pre-preparation: 55 parts of high-temperature asphalt, 15 parts of anthracene oil, 5 parts of trioxymethylene, 12 parts of aldehyde-modified nanomaterials, and 10 parts of p-toluenesulfonic acid were mixed evenly; heated to 150°C and stirred for 20 hours under a nitrogen atmosphere, and then the heating was stopped to obtain high-temperature modified asphalt;

[0051] Step 1: dry-mix 75 parts of calcined petroleum coke (40 parts of calcined petroleum coke A and 35 parts of calcined petroleum coke B) and 25 parts of electrode graphite crumbs (12 parts of electrode graphite crumbs A, 7 parts of electrode graphite crumbs B, and 6 parts of electrode graphite crumbs C), add 20 parts of high-temperature modified asphalt, heat to 150° C. and knead for 30 minutes, heat to 170° C. and knead for 15 minutes to obtain a paste;

[0052] Step 2: Cool the paste to 140°C and use vertical vibration horizontal extrusion molding process with a vertical pressure of 20 kg / cm 2 Press first and then vibrate, cool in cold water pool for 6 hours, let stand for 48 hours to obtain electrode premise;

[0053] Step 3: The electrode is calcined, during which: a 1200-hour heating curve is set to heat to 900°C, calcined for 250 hours, and naturally cooled out of the furnace to obtain a calcined product; then it is graphitized, during which: a heating rate is set to 10°C / min to heat to 2600°C, power is supplied for 60 hours, power is cut off, and cooled to obtain a large-sized graphite electrode.

[0054] Comparative Example 1: Based on Example 1, high temperature asphalt (Hebei Xiangbei) was used instead of high temperature modified asphalt, and the rest was the same as Example 1; the details are as follows:

[0055] Step 1: dry-mix 78 parts of calcined petroleum coke (45 parts of calcined petroleum coke A and 33 parts of calcined petroleum coke B) and 22 parts of electrode graphite crumbs (10 parts of electrode graphite crumbs A, 7 parts of electrode graphite crumbs B, and 5 parts of electrode graphite crumbs C), add 26 parts of high-temperature asphalt, heat to 150° C. and knead for 30 minutes, heat to 170° C. and knead for 15 minutes to obtain a paste;

[0056] Step 2: Cool the paste to 140°C and use vertical vibration horizontal extrusion molding process with a vertical pressure of 20 kg / cm 2 Press first and then vibrate, cool in cold water pool for 6 hours, let stand for 48 hours to obtain electrode premise;

[0057] Step 3: The electrode is calcined, during which: a 1250-hour heating curve is set to heat to 900°C, calcined for 250 hours, naturally cooled and taken out of the furnace to obtain a calcined product; then it is graphitized, during which: a heating rate is set to 10°C / min to heat to 2600°C, power is supplied for 60 hours, power is cut off, cooled, and a large-sized graphite electrode is obtained.

[0058] Comparative Example 2: Based on Example 1, nanomaterials are directly introduced into the high-temperature modified asphalt, and the rest is the same as Example 1; the details are as follows:

[0059] Pre-preparation: 55 parts of high-temperature asphalt, 16 parts of anthracene oil, 15 parts of trioxymethylene, 4 parts of nanomaterials, and 10 parts of p-toluenesulfonic acid were mixed evenly; heated to 150°C and stirred for 20 hours under a nitrogen atmosphere, and then the heating was stopped to obtain high-temperature modified asphalt;

[0060] Step 1: dry-mix 78 parts of calcined petroleum coke (45 parts of calcined petroleum coke A and 33 parts of calcined petroleum coke B) and 22 parts of electrode graphite crumbs (10 parts of electrode graphite crumbs A, 7 parts of electrode graphite crumbs B, and 5 parts of electrode graphite crumbs C), add 26 parts of high-temperature modified asphalt, heat to 150° C. and knead for 30 minutes, heat to 170° C. and knead for 15 minutes to obtain a paste;

[0061] Step 2: Cool the paste to 140°C and use vertical vibration horizontal extrusion molding process with a vertical pressure of 20 kg / cm 2 Press first and then vibrate, cool in cold water pool for 6 hours, let stand for 48 hours to obtain electrode premise;

[0062] Step 3: The electrode is calcined, during which: a 1250-hour heating curve is set to heat to 900°C, calcined for 250 hours, naturally cooled and taken out of the furnace to obtain a calcined product; then it is graphitized, during which: a heating rate is set to 10°C / min to heat to 2600°C, power is supplied for 60 hours, power is cut off, cooled, and a large-sized graphite electrode is obtained.

[0063] Comparative Example 3: Based on Example 1, the epoxy macromolecular silane coupling agent in the raw material for preparing the aldehyde-modified nanomaterial is replaced with γ-glycidyloxypropyltrimethoxysilane, and the rest is the same as Example 1; specifically as follows:

[0064] Pre-preparation: (1) Graphene, carbon nanotubes and molybdenum disilicide are mixed uniformly in a mass ratio of 0.6:0.3:0.1 to obtain nanomaterials; (2) 1 g of nanomaterials and 8 mL of γ-glycidyloxypropyltrimethoxysilane are added to 10 mL of anhydrous toluene, and 0.16 mL of triethylamine is added dropwise; under a nitrogen atmosphere, reflux at 110° C. for 3 hours; wash and dry to obtain modified nanomaterials; (3) 1 g of modified nanomaterials is added to 20 mL of 0.1 mol / L sulfuric acid solution, heated to 50° C. and stirred for 8 hours, filtered and washed to obtain pre-activated nanomaterials; (4) 1 g of pre-activated nanomaterials is dispersed in 20 mL of deionized water, 4.5 mL of 0.1 mol / L sodium periodate solution is added, and stirred at room temperature for 5 hours; wash and dry to obtain aldehyde-modified nanomaterials;

[0065] (5) 55 parts of high-temperature asphalt, 16 parts of anthracene oil, 5 parts of trioxymethylene, 14 parts of formaldehyde-modified nanomaterials, and 10 parts of p-toluenesulfonic acid were mixed uniformly; the mixture was heated to 150° C. and stirred for 20 hours under a nitrogen atmosphere, and the heating was stopped to obtain a high-temperature modified asphalt;

[0066] Step 1: dry-mix 78 parts of calcined petroleum coke (45 parts of calcined petroleum coke A and 33 parts of calcined petroleum coke B) and 22 parts of electrode graphite crumbs (10 parts of electrode graphite crumbs A, 7 parts of electrode graphite crumbs B, and 5 parts of electrode graphite crumbs C), add 26 parts of high-temperature modified asphalt, heat to 150° C. and knead for 30 minutes, heat to 170° C. and knead for 15 minutes to obtain a paste;

[0067] Step 2: Cool the paste to 140°C and use vertical vibration horizontal extrusion molding process with a vertical pressure of 20 kg / cm 2 Press first and then vibrate, cool in cold water pool for 6 hours, let stand for 48 hours to obtain electrode premise;

[0068] Step 3: The electrode is calcined, during which: a 1250-hour heating curve is set to heat to 900°C, calcined for 250 hours, naturally cooled and taken out of the furnace to obtain a calcined product; then it is graphitized, during which: a heating rate is set to 10°C / min to heat to 2600°C, power is supplied for 60 hours, power is cut off, cooled, and a large-sized graphite electrode is obtained.

[0069] Comparative Example 4: Based on Example 1, the nanomaterial in the high-temperature modified asphalt is a single graphene; the rest is the same as Example 1; specifically as follows:

[0070] Pre-preparation: (1) Graphene, carbon nanotubes and molybdenum disilicide are mixed uniformly in a mass ratio of 0.6:0.3:0.1 to obtain nanomaterials; (2) 1 g of nanomaterials and 8 mL of epoxy macromolecular silane coupling agent are added to 10 mL of anhydrous toluene, and 0.16 mL of triethylamine is added dropwise; under a nitrogen atmosphere, reflux at 110° C. for 3 hours; wash and dry to obtain modified nanomaterials; (3) 1 g of modified nanomaterials is added to 20 mL of 0.1 mol / L sulfuric acid solution, heated to 50° C. and stirred for 8 hours, filtered and washed to obtain pre-activated nanomaterials; (4) 1 g of pre-activated nanomaterials is dispersed in 20 mL of deionized water, 4.5 mL of 0.1 mol / L sodium periodate solution is added, and stirred at room temperature for 5 hours; wash and dry to obtain aldehyde-modified nanomaterials;

[0071] (5) 55 parts of high-temperature asphalt, 16 parts of anthracene oil, 5 parts of trioxymethylene, 14 parts of formaldehyde-modified nanomaterials, and 10 parts of p-toluenesulfonic acid were mixed uniformly; the mixture was heated to 150° C. and stirred for 20 hours under a nitrogen atmosphere, and the heating was stopped to obtain a high-temperature modified asphalt;

[0072] Step 1: dry-mix 78 parts of calcined petroleum coke (45 parts of calcined petroleum coke A and 33 parts of calcined petroleum coke B) and 22 parts of electrode graphite crumbs (10 parts of electrode graphite crumbs A, 7 parts of electrode graphite crumbs B, and 5 parts of electrode graphite crumbs C), add 26 parts of high-temperature modified asphalt, heat to 150° C. and knead for 30 minutes, heat to 170° C. and knead for 15 minutes to obtain a paste;

[0073] Step 2: Cool the paste to 140°C and use vertical vibration horizontal extrusion molding process with a vertical pressure of 20 kg / cm 2 Press first and then vibrate, cool in cold water pool for 6 hours, let stand for 48 hours to obtain electrode premise;

[0074] Step 3: The electrode is calcined, during which: a 1250-hour heating curve is set to heat to 900°C, calcined for 250 hours, naturally cooled and taken out of the furnace to obtain a calcined product; then it is graphitized, during which: a heating rate is set to 10°C / min to heat to 2600°C, power is supplied for 60 hours, power is cut off, cooled, and a large-sized graphite electrode is obtained.

[0075] Performance test: The large-scale graphite electrodes prepared in the examples and comparative examples, with a size of 900×900×2200 mm, were subjected to relevant performance tests; the specific results are as follows:

[0076] sample <![CDATA[Resistivity μΩ . m]]> Flexural strength MPa <![CDATA[Bulk density g / cm 2 > <![CDATA[Coefficient of thermal expansion × 10 -6 / °C]]> Example 1 8.7 12.8 1.78 2.61 Comparative Example 1 11.2 10.7 1.58 2.95 Comparative Example 2 10.2 11.5 1.64 2.88 Comparative Example 3 9.9 11.8 1.68 2.80 Comparative Example 4 9.3 12.1 1.70 2.73

[0077] Conclusion: From the data in the above table, it can be seen that: the present application has prepared a large-scale graphite electrode with low resistivity, high strength and high thermal performance; it can effectively ensure that the two electrodes are closely butted and evenly communicated, and the safety of the electrode is achieved when used in an industrial silicon furnace. From the data of Comparative Examples 1 to 4 compared with Example 1, it can be seen that in Comparative Example 1, the direct use of high-temperature asphalt has greatly reduced the relevant performance. In Comparative Example 2, due to the direct introduction of nanomaterials, polycarbosilane and other chain segments were introduced during the unmodified process, the residual carbon rate and the graphitization furnace were reduced, resulting in a decrease in performance. In Comparative Example 3, due to the use of small molecule γ-glycidyloxypropyltrimethoxysilane, the cohesive viscosity was reduced, the density and the residual carbon rate were reduced, and the relevant performance was reduced. In Comparative Example 4, since the nanomaterial is only a single graphene, the relevant sintering performance is reduced, and the conductivity and the like are slightly reduced.

[0078] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing large-scale graphite electrodes for metal silicon smelting, characterized in that: The following steps are involved: Step 1: Evenly dry-mix calcined petroleum coke and electrode graphite, add high-temperature modified asphalt, heat to 140-150° C. and knead for 15-30 minutes, heat to 160-170° C. and knead for 10-20 minutes to obtain a paste; Step 2: Cool the paste to 130-140℃, and use vertical vibration horizontal extrusion molding process with vertical pressure of 17-22 kg / cm 2 Press first and then vibrate, cool in cold water pool for 6-8 hours, let stand for 48 hours to obtain electrode prerequisites; Step 3: calcining and graphitizing the electrode to obtain a large-sized graphite electrode.

2. The method for preparing a large-scale graphite electrode for metal silicon smelting according to claim 1, characterized in that: During the calcination process, a heating curve of 1100 to 1250 hours is set to heat to 880 to 900°C, and the product is calcined for 200 to 300 hours, cooled naturally and taken out of the furnace to obtain a calcined product; during the graphitization process, a heating rate of 10 to 15°C / min is set to heat to 2400 to 2800°C, power is supplied for 50 to 80 hours, power is cut off, and the product is cooled to obtain a large-sized graphite electrode.

3. The method for preparing a large-scale graphite electrode for metal silicon smelting according to claim 1, characterized in that: The raw materials of the paste include the following components: by weight, 75-80 parts of calcined petroleum coke, 20-25 parts of electrode graphite chips, and 20-30 parts of high-temperature modified asphalt; The calcined petroleum coke includes materials of the following particle sizes: 40 to 50 parts of calcined petroleum coke A with a size of 1 to 10 mm, and 30 to 35 parts of calcined petroleum coke B with a size of 0.1 to 0.15 mm; the electrode graphite fragments include materials of the following particle sizes: 9 to 12 parts of electrode graphite fragments A with a size of 0.1 to 4 mm, 5 to 7 parts of electrode graphite fragments B with a size of 4 to 8 mm, and 4 to 6 parts of electrode graphite fragments C with a size of 8 to 15 mm.

4. The method for preparing a large-scale graphite electrode for metal silicon smelting according to claim 1, characterized in that: The preparation method of the high temperature modified asphalt is: Step 1: (1) Add nanomaterials and epoxy macromolecular silane coupling agent to anhydrous toluene, and drop triethylamine; reflux at 110-115° C. for 2-3 hours under nitrogen atmosphere; wash and dry to obtain modified nanomaterials; (2) Add the modified nanomaterials to 0.1-0.12 mol / L sulfuric acid solution, heat to 50-55° C., stir for 6-8 hours, filter and wash to obtain preactivated nanomaterials; (3) Disperse the preactivated nanomaterials in deionized water, add 0.1-0.12 mol / L sodium periodate solution, stir at room temperature for 4-6 hours; wash and dry to obtain aldehyde-modified nanomaterials; Step 2: Evenly mix the high-temperature asphalt, anthracene oil, trioxymethylene, aldehyde-modified nanomaterials, and p-toluenesulfonic acid; in a nitrogen atmosphere, heat to 140-160° C. and stir for 18-24 hours, then stop heating to obtain high-temperature modified asphalt.

5. The method for preparing a large-scale graphite electrode for metal silicon smelting according to claim 4, characterized in that: The nano material comprises graphene, carbon nanotube and molybdenum disilicide in a mass ratio of 0.5-0.6:0.2-0.3:0.

1.

6. The method for preparing a large-scale graphite electrode for metal silicon smelting according to claim 4, characterized in that: The raw materials of the high-temperature modified asphalt include the following components: by mass, 55 parts of high-temperature asphalt, 15-20 parts of anthracene oil, 5-8 parts of trioxymethylene, 12-15 parts of formaldehyde-modified nanomaterials, and 10-12 parts of p-toluenesulfonic acid.

7. The method for preparing a large-scale graphite electrode for metal silicon smelting according to claim 4, characterized in that: In the raw materials of the modified nanomaterial, the ratio of the nanomaterial, the epoxy macromolecular silane coupling agent, and the triethylamine is 1g: 6-8mL: 0.15-0.18mL; in the raw materials of the preactivated nanomaterial, the ratio of the modified nanomaterial and the sulfuric acid solution is 1g: 18-20mL; in the raw materials of the formaldehyde-treated nanomaterial, the ratio of the preactivated nanomaterial, deionized water, and the sodium periodate solution is 1g: 18-20mL: 4-4.5mL.

8. The method for preparing a large-scale graphite electrode for metal silicon smelting according to claim 4, characterized in that: The preparation method of the epoxy macromolecular silane coupling agent is: S1-1: Sodium sand, 1,2-dimethyl-1,1,2,2-tetrachlorodisilane, and diethylene glycol dimethyl ether are sequentially added to tetrahydrofuran, and stirred at room temperature for 5 to 8 minutes under a nitrogen atmosphere; the temperature is raised to 40 to 50°C; methylvinyldichlorosilane, methylphenyldichlorosilane, and dibromomethane are added dropwise; after the addition is completed, the reaction is continued for 3 to 4 hours; chlorodimethylsilane borate and trimethylchlorosilane are added sequentially, and stirring is continued for 0.5 to 1 hour; suction filtration, washing, and reduced pressure distillation are performed to obtain liquid vinyl polycarbosilane; S1-2: Add liquid vinyl polycarbosilane and formic acid to toluene, add concentrated sulfuric acid dropwise; raise the temperature to 30-35°C, add hydrogen peroxide dropwise; raise the temperature to 60-70°C to react for 4-6 hours; wash to neutrality, evaporate the solvent, and obtain epoxy polycarbosilane; S1-3: Add epoxy polycarbosilane, amino silane coupling agent and ferrocenylamine to toluene in sequence, raise the temperature to 60-65° C. and react for 6-8 hours, evaporate the solvent to obtain an epoxy macromolecular silane coupling agent.

9. The method for preparing a large-scale graphite electrode for metal silicon smelting according to claim 8, characterized in that: The raw materials of the liquid vinyl polycarbosilane include the following components: by mass fraction, 3 to 4 parts of sodium sand, 3 to 5 parts of 1,2-dimethyl-1,1,2,2-tetrachlorodisilane, 14 to 17 parts of methylvinyldichlorosilane, 12 to 15 parts of methylphenyldichlorosilane, 34 to 38 parts of dibromomethane, 6 to 8 parts of chlorodimethylsilane borate, 4 to 6 parts of trimethylchlorosilane, 5 to 10 parts of diethylene glycol dimethyl ether, and 125 to 130 parts of tetrahydrofuran; The raw materials of the epoxy polycarbosilane include the following components: by mass fraction, 10 parts of liquid vinyl polycarbosilane, 1.5-1.8 parts of formic acid, 0.2-0.5 parts of concentrated sulfuric acid, and 6-7 parts of hydrogen peroxide; the raw materials of the epoxy macromolecular silane coupling agent include 10 parts of epoxy polycarbosilane, 0.3-0.5 parts of aminosilane coupling agent, and 0.05-0.08 parts of ferroceneamine.

10. A large-sized graphite electrode prepared by the method for preparing a large-sized graphite electrode specially used for metallic silicon smelting according to claim 1.

Citation Information

Cited By

  • Graphene-graphite electrode preparation method and graphene-graphite electrode

    CN120483719A